Supercharged Python : take your code to the next level - Overland, Brian, 1958-; Bennett, John (Addison-Wesley Professional, 2019)
"Brian Overland makes programming simple. ... To my amazement, his books explain complicated code clearly enough for anyone to understand."--Art Sedighi, PhD Tapping into the full power of Python doesn't have to be difficult. Supercharged Python is written for people who've learned the fundamentals of the language but want to take their skills to the next level. After a quick review of Python, the book covers: advanced list and string techniques; all the ways to handle text and binary files; financial applications; advanced techniques for writing classes; generators and decorators; and how to master packages such as Numpy (Numeric Python) to supercharge your applications! Use profilers and "magic methods" to code like a pro Harness the power of regular expressions to process text quickly with a single statement Take advantage of 22 coding shortcuts, along with performance tips, to save time and optimize your code Create really useful classes and objects, for games, simulations, money, mathematics, and more Use multiple modules to build powerful apps while avoiding the "gotchas" Import packages to dramatically speed up statistical operations-by as much as 100 times! Refer to the five-part language reference to look up fine points of the language Supercharged Python demonstrates techniques that allow you to write faster and more powerful code, whether you're manipulating large amounts of data or building sophisticated applications. Register your book for convenient access to downloads, updates, and/or corrections as they become available. See inside book for details